The Potential Reach of Opioid Substitution Settings to Deliver HCV Care to People Who Inject Drugs in Australia - Butler, K.; Day, C.; Dietze, P.; Bruno, R.; Alati, Rosa; Burns, L. (Elsevier Inc., 2015)
© 2015 Elsevier Inc.. Background: Recent efforts in Australia to engage people who inject drugs (PWID) in hepatitis C (HCV) care have focussed on opioid substitution treatment (OST) services as a delivery site. This approach potentially excludes non-opioid using PWID. This study aimed to determine differences between those currently receiving OST and those not among a sample of PWID. Methods: Additional questions on HCV testing were included in the 2013 Illicit Drug Reporting System (IDRS), an annual sentinel surveillance system. The IDRS recruits PWID in all Australian capital cities from a range of sources, predominantly needle and syringe programs. All participants are reimbursed AUD$40 for a ~. 45. minute interview-administered survey. Results: Current OST was reported by 44% of the total sample, and two-thirds reported an opioid as their drug of choice. Those participants who reported current OST were significantly more likely than those not in OST to report heroin as their drug of choice (65% vs. 43%, p < 0.0.001) and the drug injected most often (53% vs. 30%, p < 0.001). Compared to those in OST, those not in OST were more likely to report methamphetamine as their drug of choice (29% vs. 14%, p < 0.001) or drug injected most often (33% vs. 17%, p < 0.001). Current OST clients were more likely to have been tested for HCV antibodies (anti-HCV) than those not in OST (96% vs. 93%, p < 0.05) and to report an anti-HCV positive result (75% vs. 64%, p < 0.001). Those receiving OST were no more likely than those not to undergo further HCV-related testing (e.g. RNA) (62% vs. 56%, p=. 0.136). Both groups reported further HCV-related testing was undertaken primarily at a community general practice. Discussion: Despite a large proportion of current PWID receiving OST, there remains a substantial minority who are neither seeking nor eligible for treatment. Efforts to improve access to HCV care for PWID in Australia therefore need to be expanded beyond OST, especially given the large proportion of participants who reported inadequate HCV testing.